PEMIDANAAN TERHADAP MILITER YANG MELAKUKAN TINDAK PIDANA LALU LINTAS YANG MENGAKIBAT KEMATIAN (STUDI KASUS PUTUSAN NOMOR 38-K/PM.I- 02/AD/IV/2023): Sentencing Of Military Personnel Who Commit Traffic Crimes Resulting In Death (Case Study Of Decision Number 38-K/PM.I- 02/AD/IV/2023) - Dhimas Indra Anggoro; Prastopo (Faculty of Law, Universitas Trisakti, 2025)
Traffic accidents are regulated in Article 1 Number 24 of Law Number 22 of 2009 concerning Traffic. It was recorded that 3,168 TNI soldiers were involved in traffic accidents in 2023. What kind of punishment is expected or appropriate for TNI soldiers who commit criminal acts of negligence resulting in death? Based on the provisions of Article 310 paragraph (3) Juncto Paragraph (4) of Law Number 22 of 2009 concerning Traffic and Road Transportation, does the judge's decision in decision number 38-K/PM.I-02/AD/IV/2023 support the goal of criminalization? (Study of Decision Number 38-K/PM.I-02/AD/IV/2023). This study will describe and analyze the expected or appropriate punishment for TNI members who commit traffic crimes resulting in death in Decision Number 38-K / PM.I-02 / AD / IV / 2023 to determine whether the judge's considerations in the decision are in accordance with Article 310 Paragraph (3) Juncto (4) Law Number 22 of 2009 concerning Traffic and Road Transportation. This study uses normative law, namely research conducted by searching for secondary data or library sources. The method used to collect information in this study is by means of a literature review. In order to protect the public and enforce the law, the Military Auditor filed a lawsuit with the Panel of Judges by imposing a prison sentence of 10 (ten) months minus the detention period. Meanwhile, the defendant Jaswajul in Decision Number 38-K / PM.I-02 / AD / IV / 2023 was sentenced to 3 (three) months in prison with a probationary period of 5 (five) months. This is based on the findings of data analysis.